Effect of Yoga Practices in Reducing Aggression and Counterproductive Work Behavior: A Randomized Controlled Trial - Dwivedi, Umesh; Kumari, Sony; Akhilesh, K. B.; Nagendra, H. R. (Prabandhan: Indian Journal of Management, 2015)
Counterproductive work behavior (CWB) in the workplace can take numerous forms, starting from difficult personality traits that harm team cohesion to damaging property that undermines an organization’s financial well-being. Aggression has been consistently shown to correlate with incidents of CWB and also mediates the relationship between CWB and its predictors. Yoga is a mind and body practice with a goal of unifying emotional, psychological, and physical selves. Findings of yoga research recommend that yoga based techniques may be helpful for working professionals in moving and managing feelings of anger and frustration. The present study examined the effect of yoga on working professionals in reducing aggression and counterproductive work behavior. A pretest-post test research design of 10-week duration was used for two cohorts, randomized into a yoga group and a control group with 80 subjects in each group. The yoga group practiced asanas, pranayama, meditation, and yogic theory lectures. Mild to moderate physical exercises and management lectures were taught to the control group. The data was analyzed using SPSS, and the results revealed that the yoga group showed statistically significant reduction (p < 0.001) in aggression and counterproductive work behaviors in comparison to the control group. The paper contributes by introducing a cost-effective way to prevent heavy losses organizations are incurring due to counterproductive work behaviors. The results also suggested that having regular yoga sessions at a workplace can result in happier home lives and increased productivity.